Muslim saints of South Asia : the eleventh to fifteenth centuries - Suvorova, A. A. (Anna Aronovna) (RoutledgeCurzon Sūfī series., 2004)
This book studies the veneration practices and rituals of the Muslim saints. It outlines trends of the main Sufi orders in India, the profiles and teachings of the famous and less known saints, and the development of pilgrimages.